Impact of leptin receptor gene variants on risk of non-alcoholic fatty liver disease and its interaction with adiponutrin gene - Cheah, Phaik Leng; Zain, S.M.; Mohamed, Z.; Mahadeva, S.; Rampal, S.; Chin, K.F.; Mahfudz, A.S.; Basu, R.C.; Tan, H.L.; Mohamed, R. (Wiley, 2013)
Genetic polymorphism has been implicated as a factor for the occurrence of non-alcoholic fatty liver disease (NAFLD). This study attempted to assess whether polymorphisms in the leptin receptor(LEPR) gene and its combined effect with patatin-like phospholipase domain-containing protein 3(PNPLA3/adiponutrin) are associated with risk of NAFLD.A total of 144 biopsy-proven NAFLD and 198 controls were genotyped using the Sequenom MassARRAY platform. We observed a significant association between the LEPR rs1137100 and rs1137101 with susceptibility to NAFLD (odds ratio [OR] 1.64, 95% confidence interval [CI] 1.18-2.28, P = 0.003; and OR 1.61, 95% CI 1.11-2.34, P = 0.013, respectively) and to non-alcoholic steatohepatitis (OR 1.49,95% CI 1.05-2.12, P = 0.026; and OR 1.57, 95% CI 1.05-2.35, P = 0.029, respectively). The LEPR rs1137100 is also associated with simple steatosis (OR 2.27, 95% CI 1.27-4.08, P = 0.006). Analysis of gene-gene interaction revealed a strong interaction between the LEPR and PNPLA3 genes(empirical P = 0.001). The joint effect of LEPR and PNPLA3 greatly exacerbated the risk of NAFLD(OR 3.73, 95% CI 1.84-7.55, P < 0.0001). The G allele of rs1137100 is associated with lower fibrosis score (OR 0.47, 95% CI 0.28-0.78, P = 0.001).We report an association between variants of LEPR rs1137100 and rs1137101 with risk of NAFLD. This study suggests that rs1137100, specifically the G allele, is associated with a less severe form of liver disease in patients with NAFLD. The interaction between LEPR and PNPLA3 genes showed increased risk of NAFLD compared to either gene alone.